Continued breastfeeding and work: scenario of maternal persistence and resilience - Isília Aparecida Silva; Carla Marins Silva; Elisiany Mello Costa; Micheli de Jesus Ferreira; Erika de Sá Vieira Abuchaim (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to understand the challenges in mothers' daily life and strategies adopted to reconcile activities outside the home and continued breastfeeding. Methods: a cross-sectional, qualitative study. Theoretical-methodological assumptions were discursive practices and production of meanings in everyday life. Participants were 22 women from a specific social media group who had breastfed at least one child for >7 months. Data were collected between November 2020 and March 2021. Results: themes: Around the world of activities outside the home; Work environment: routines, opportunities and difficulties to maintain breastfeeding. Final Considerations: women's experiences reveal a daily life with difficulties in reconciling the desire to breastfeed and the work scenario. Support network and adaptation to children's food routine were strategies adopted to minimize risks of weaning. The results show the need to consolidate policies to encourage continued breastfeeding in the labor market.